Students’ Layer of Mathematical Understanding on the Material of Linear Equation One Variable in Terms of Self-Directed Learning - Fadilah, Dea Aulia Nur; Elis Nurhayati; Redi Hermanto (International Journal of Applied Learning and Research in Algebra, 2024)
This study aims to describe students' mathematical understanding in working on mathematical understanding test questions on the material of linear equations of one variable. The research method used in this research is descriptive method. The data collection technique of this research, namely distributing self-directed learning questionnaires, giving mathematical understanding tests, and conducting interviews. The research subjects were selected from VIII E students of SMP Negeri 4 Tasikmalaya as many as three people based on the results of the questionnaire that fulfils one category each of high, medium, low and the results of the mathematical understanding test that most meet the indicators of mathematical understanding. Data analysis techniques used, namely data reduction, data presentation, and conclusion drawing. The results showed that subjects with high self-directed learning category (S28) could work on problems with coherent, structured, complete answers up to the inventizing layer with intervention at the inventizing layer. Subjects with moderate self-directed learning category (S31) can work on problems with correct answers up to the structuring layer with intervention at the noticing property layer. Subjects with low self-directed learning category (S6) can work on the problem but not completely until the image making layer with intervention on the image making layer. Keywords: Linear equation one variable; Mathematical understanding; Pirie-Kieren; Self-Directed Learning.